Broad ligament myoma at 75 causing clinical, ultrasonic and intraoperative diagnostic dilemma - Gadre, Sandhya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
This case is reported because of the diagnostic dilemma it caused. This is a report of a 75 years postmenopausal female with epigastric pain & old USG report of 4 cms mass in right adnexa, ? neoplastic, done 1 year back. Clinically uterus was atrophic with 4 cms mass in right fornix, mobile, nontender, separate from uterus. CA 125=19.7 U/L. USG showed right adnexal mass of about 4 cms, anechoic, right ovary was not seen separately, suggestive of right ovarian mass, left ovary normal. Laparotomy was done with provisional diagnosis of persistent postmenopausal ovarian mass. During the procedure the same mass was seen attached to right cornu of uterus. Right ovary was not seen separately. TAH with BSO was done. On dissecting the specimen, the mass & right ovary were found entrapped together in leaves of broad ligament. The ovary & the mass were in close proximity of each other appearing as one; pedicle of the mass was seen attached to right cornu of uterus with a peduncle; quite separate from right ovarian ligament but in its close proximity, both appearing as one. Histopathology report suggested it to be leiomyoma.